Surely surely Marisol Rainey - Kelly, Erin Entrada 1977- (Greenwillow Books, an imprint of HarperCollinsPublishers, 2022)
"One of Marisol's least-favorite things is gym class--especially when Coach Decker announces that they will be playing kickball--so Marisol and her best friend Jada ask the best (and stinkiest) athlete they know--Marisol's big brother Oz--for help"--
Keywords: Freundschaft; Ball; Selbstvertrauen; Spiel; Kickball / Juvenile fiction; Self-confidence / Juvenile fiction; Best friends / Juvenile fiction; Friendship / Juvenile fiction; Confiance en soi / Romans, nouvelles, etc. pour la jeunesse; Amis / Romans, nouvelles, etc. pour la jeunesse; Amitié / Romans, nouvelles, etc. pour la jeunesse; JUVENILE FICTION / Social Themes / Friendship; JUVENILE FICTION / Social Themes / Self-Esteem & Self-Reliance; JUVENILE FICTION / Humorous Stories